Volume 5: High-Pressure Technology; ASME NDE Division 2012
DOI: 10.1115/pvp2012-78509
|View full text |Cite
|
Sign up to set email alerts
|

New Manufacturing Cycle to Improve the Life of Packing Cups for Hyper-Compressors

Abstract: Hyper-compressors are subjected to very high operating pressure, maximum and fluctuating, strongly impacting design and life of all cylinder components. Components subjected to fatigue (both high cycle fatigue and low cycle fatigue) can experience a failure in a very short time that may cause large production losses. Packing cups proved to be one of the most critical cylinder components and the fatigue behavior of the packing cups subjected to alternating loads, due to the suction and discharge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In order to investigate the stress state of the lube oil ducts, the Lame's equations were used [5]. Using …”
Section: Stress Calculation By Using the Lame's Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to investigate the stress state of the lube oil ducts, the Lame's equations were used [5]. Using …”
Section: Stress Calculation By Using the Lame's Equationmentioning
confidence: 99%
“…The fatigue cracks usually initiate from the surface defects such as fretting and machine marks [2]. Maggi et al showed that the typical failure modes of packing cups are tangential or radial [5].…”
Section: Introductionmentioning
confidence: 99%